ACCOUNTING OF CAPITAL AND LIABILITIES IN THE CONTEXT OF DIGITALIZATION AND TRANSITION TO INTERNATIONAL FINANCIAL REPORTING STANDARDS - Maxim Kodirov (Web of Journals Publishing, 2023)
The processes of digitalization and transition to international financial reporting standards are associated with significant systemic changes that transform accounting processes in the company. Today, it is already difficult to imagine the work of any company without the use of electronic document management (EDI). In the current accounting process, EDI and digitalization include personnel, financial, management accounting, work with archival documents and many other accounting processes. For JSC "Uzbekiston Temir yillari" with a distributed management structure and the presence of structural divisions, it is very important to effectively organize the management of all these processes. The transition to international financial reporting standards is associated with solving a number of problems, including in the regulation of accounting for capital and liabilities. The issues of the impact of international financial reporting standards on the development of the domestic accounting system are related to the digitalization of economic processes and the emergence of new accounting objects and increased requirements for the quality of generated reporting. The article analyzes the essence of the newly emerged accounting categories, compares the definitions of "liabilities" in international standards and domestic practice. It is revealed that the gaps in the accounting of capital and liabilities are caused by insufficient establishment of the conceptual apparatus, the presence of estimated values, the use of professional judgment of an accountant affecting the quality of information in the reporting, the lag of legislative regulation in terms of accounting for digital objects as authorized capital. The issues of accounting and reporting of social business operations are considered. Possible ways of solving the problems of liability accounting are presented, including the unification of the conceptual apparatus, the modernization of the accounts, the development of recommendations regarding the application of professional judgment to the accountant, the expansion of requirements for the list of information on the activities of an economic entity presented in accounting statements, as well as the application of international standards.
Keywords: liabilities, capital, liabilities, digitalization, accounting problems, accounting, accounting reform, International Financial Reporting Standards.